Pluralistic Task Shifting for a More Timely Cancer Diagnosis - Hans Thulesius; Ulrika Sandén Sandén; Davorina Petek Petek; Robert Hoffman Hoffman; Tuomas Koskela; Bernardino Oliva-Fanlo; Ana Luisa Neves; Senada Hajdarevic; Lars Harrysson; Berit Skjodeborg Toftegaard Toftegaard; Peter Vedsted Vedsted; Michael Harris Harris (Grounded Theory Review: An International Journal)
Objective: To explore how cancer could be diagnosed in a more timely way. Design: Classic grounded theory analysis of primary care physicians’ free text survey responses to: “How do you think the speed of diagnosis of cancer in primary care could be improved?” and secondary analysis of primary care physician interviews, survey responses, literature. Setting: Primary care in 20 European Örenäs Research Group countries. Subjects: Primary care physicians: 1352 survey respondents (2013-2016), 20 Spanish and 7 Swedish interviewees (2015-2019). Main outcome measures: Conceptual explanation of how to improve timeliness of cancer diagnosis. Results: Pluralistic task shifting is a grounded theory of a composite strategy. It includes task sharing - among nurses, physicians, nurse assistants, secretaries and patients - and changing tasks with cancer screening when appropriate or cancer fast-tracks to accelerate cancer case finding. A pluralistic dialogue culture of comprehensive collaboration and task redistribution is required for effective pluralistic task shifting. Pluralistic task shifting relies on cognitive task shifting, which includes learning more about slow analytic reasoning and fast automatic thinking initiated by pattern recognition; and digital task shifting, which by use of eHealth and telemedicine bridges time and place and improves power symmetry between patients, caregivers and clinicians. Financial task shifting that involves cost tracking followed by reallocation of funds is necessary for the restructuring and retraining required for successful pluralistic task shifting. A timely diagnosis reduces expensive investigations and waiting times. Also, late-stage cancers are costlier to treat than early stage cancers. Timing is central to cancer diagnosis: not too early to avoid overdiagnosis, and never too late. Conclusions: We present pluralistic task shifting as a conceptual summary of strategies needed to optimise the timeliness of cancer diagnosis.